MARITAL SATISFACTION AND ITS RELATIONSHIP TO AGE, LENGTH OF RELATIONSHIP, AND THE PRESENCE OF CLINICAL SYMPTOMS - Marcia Fortes Wagner; Karine Klann; Bianca Vasconcellos Protti; Cláudia Mara Bosetto Cenci; Camila Rosa de Oliveira; Luís Henrique Paloski (Artefactum - revista de estudos interdisciplinares, 2026)
Marital satisfaction is an important protective factor for physical and mental health, as it is associated with greater well-being, a stronger immune system, and increased longevity among partners. On the other hand, marital dissatisfaction has been linked to the development of symptoms of depression, anxiety, and stress. The aim of this study was to investigate the correlation between clinical symptoms (depression, anxiety, and stress) and marital satisfaction, while also considering sociodemographic variables such as age and relationship duration. Forty individuals participated, with a mean age of 29 years (SD = 9.02), all in stable relationships, marriages, or common-law marriages, who completed the Marital Life Satisfaction Assessment Scale (EASAVIC) and the Depression Anxiety Stress Scale (DASS-21). Regarding the EASAVIC, the dimension of marital life satisfaction with the highest mean score was Love: trust, perception of the other’s feelings, and perspectives, followed by Love: physical and psychological characteristics. The DASS-21, on the other hand, indicated the presence of a significant percentage of depressive, anxiety, and stress symptoms ranging from mild to extremely severe. A negative correlation was found between age and marital satisfaction, particularly in factors related to attention, communication, emotional support, and physical and psychological characteristics. There was no significant correlation between relationship duration and marital satisfaction. The findings suggest that emotional and individual factors have a greater influence on marital quality than demographic variables, highlighting the importance of interventions focused on emotional health and communication between partners.